Red-emitting Ba2Si5N8Eu2+ conversion phosphor: A new selection for enhancing the optical performance of the in-cup packaging MCW-LEDs. Issue 1 (1st January 2018) - Tin, Phu Tran; Khanh Nhan, Nguyen Huu; Quang Minh, Tran Hoang; Thi Phuong Thao, Nguyen
Abstract: In this research, the influence of the red-emitting Ba2 Si5 N8 Eu 2+ convention phosphor on the optical performance of the 7, 000 K and 7, 700 K in-cup packaging multi-chip white LEDs (MCW-LEDs) is investigated. The effect of the red-emitting Ba2 Si5 N8 Eu 2+ convention phosphor is demonstrated based on Mie Theory by Mat Lab and Light Tools software. The research results indicated that the optical performance of MCW-LEDs was crucially affected by the red-emitting Ba2 Si5 N8 Eu 2+ phosphor's concentration. This paper provides an essential recommendation for selecting and developing the phosphor materials for MW-LEDs manufacturing.